Perceptions of use of the concept of Mediterranean diet, potential misuse and prospects to explore - Real, Helena; Graça, Pedro (Revista Española de Comunicación en Salud, 2019)
The distinction of the Mediterranean Diet as an Intangible Cultural Heritage of Humanity by UNESCO has made it possible to intensify the research and communication of this cultural model, highlighting the interest in using it in several areas. Objectives: To identify perceptions about the Mediterranean Diet concept use, potential misuse and to list prospects to explore. Methodology: Thirteen semi-structured questionnaires were applied to personalities representative of the Mediterranean Diet, from Algarve-Portugal. The interview audio was recorded, transcribed, thematically coded and analyzed. Results: Interviewees consider using the concept, especially in the areas: Agriculture/agronomy, Environment, Food, Conviviality, Culture, Economy, Pharmaceuticals, Politics, Health and Tourism. They identified as potential undue uses situations in areas such as food, gastronomy, food industry and food advertising. As prospects for future exploration, it was necessary to invest in agronomy and sustainability; food, health and economic policies; certification and regulation of the use of the concept; culture and tourism and education and communication of the concept. Conclusions: It will be important to promote a global reflection and a standardization of language for a more effective communication of the Mediterranean Diet; promote measures aimed at minimizing the current misuse of the concept, which impedes quality communication; promote its best use so that it can be promoted and safeguarded.
Keywords: Qualitative analysis; Mediterranean Diet; Future perspectives; Concept misuse; Concept use